)Qæ(NZ ^ERWNEWOGO PLINU(B. (NsERÆQ WÆR[ÆW(B-(NPRISWQT PISXMENNIKOWÆ(B, (NDIPLOMATOWÆ TA ADWOKATOWÆ tEODOTU gALÆPU (B/s)E - (NgRIGOR^UK(B-(NwOJTKO(B, (Nn(B. (Nw(B.s ((NnATAL)QÆQ wOLODIMIRÆWNA(B)s)E; (NdEM^ENKO(B, (Nw(B. (Ng(B.s ((Nw)QÆTALÆJ gRIGOROWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NpAN^UK(B, (Ns(B. (Nm(B.s ((NsTEPAN mIHAJLOWI^(B)s; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2023)
(NdO SER)QÆÇ (S0æ(NZ ^ERWNEWOGO PLINU(S1 (B((NWÆR[Æ(B-(NPRISWQTI PISXMENNIKOWÆ(B, (NDIPLOMATOWÆ TA ADWOKATOWÆ tEODOTU gALÆPU(B) (NWWÆJ[LI TWORI(B: (NnATALÆÇ gRIGOR^UK(B-(NwOJTKO(B, (NwASILQ dVURANA(B, (NwÆTALÆQ dEM^ENKA(B, (NsTEPANA pAN^UKA TA PÆSLQMOWA PRO gALÆPA nIKOLAQ wASILXKA(B.s)E
(NpRO)QÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nspus)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E